Impact of Lu-176 on the daily energy resolution quality control of a LYSO PET/CT (Revista de Física Médica, 2016)
After a retrospective analysis of the daily quality control results, an increasing trend on the energy resolution is observed. In this paper we propose as a reason for this phenomenon the activity variation of the 22Na source used in the daily quality controls relative to the intrinsic activity of the 176Lu present in the LYSO scintillator crystals. To this end, the relative activities of the isotopes have been measured and both spectra deposited in the LYSO crystals have been obtained using PENELOPE Monte Carlo package. The combined spectrum variation with time is obtained and the FWHM of the 511 keV peak has been measured each month for two years.An activity ratio 176Lu/22Na = 0.057 has been measured. With this result, a variation on the energy resolution of about 1% per year has been obtained, which is in agreement with the experimental results. Anyway, the clinical implications of this effect would be negligible as soon as the FDG dose regime is high enough compared to the concentration of 0.3 kBq/ml for which the 176Lu activity has direct effect on the measurement of random events.